Dopamine agonists for idiopathic hyperprolactinaemia and prolactinoma in adults - Nunes-Nogueira, Vania Santos [UNESP]; Gomes, Paula Lustoza; da Silva, Edina M.K.; Atallah, Álvaro N. (Wiley, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of dopamine agonists for idiopathic hyperprolactinaemia and prolactinoma in adults.